NLO QCD and EW corrections to vector-boson scattering into ZZ at the LHC - Ansgar Denner; Robert Franken; Mathieu Pellen; Timo Schmidt (Journal of High Energy Physics, 2020)
Abstract We present the first calculation of the full next-to-leading-order electroweak and QCD corrections for vector-boson scattering (VBS) into a pair of Z bosons at the LHC. We consider specifically the process pp → e+e − μ + μ − jj + X at orders O $$ \mathcal{O} $$ (α 7) and O $$ \mathcal{O} $$ (α s α 6) and take all off-shell and interference contributions into account. Owing to the presence of enhanced Sudakov logarithms, the electroweak corrections amount to −16% of the leading-order electroweak fiducial cross section and induce significant shape distortions of differential distributions. The QCD corrections on the other hand are larger (+24%) than typical QCD corrections in VBS. This originates from considering the full computation including tri-boson contributions in a rather inclusive phase space. We also provide a leading-order analysis of all contributions to the cross section for pp → e+e − μ + μ − jj + X in a realistic setup.